Performance Evaluation of Platforms Using Software Metrics - Aparna, KS; K, Vaibhav Kumar; G, Sushmitha; Saikiran, Vanam (International Journal of Computer Sciences and Engineering, 2020)
In this paper, the quality of software and its performance is evaluated using software metrics. The software product estimation is purely based on software metrics and is being applied on java and python platforms. Number of lines of code (NLOC), Cyclomatic complexity number (CCN), Token count and parameter count have been utilized to analyze the complexity of a program. The application is developed to test the codes of two different platforms and their complexities are compared using doubly linked list program as an example. The results are recorded and compared based on these software metrics to uncover the vary in results for similar projects. The paper is divided into five sections. In section one we are discussing about software metrics and it's importance in deciding the performance of different programming platforms. In section two we are discussing about different software metrics that are used to evaluate the performance of the programs. In section 3 we are discussing the previous works and related works. In section four we are taking an example and trying to evaluate the performance of the programs that are written in java and python languages and discussing about the results. In section five we are discussing about the future work and the conclusion of our developed tool.